Prediction of buffalo bull fertility based on sperm motion traits, function tests and expression of heparin binding protein - SINGH, A K; BRAR, P S; CHEEMA, RANJNA S; KUMAR, PRADEEP (The Indian Journal of Animal Sciences, 2017)
Selection of good fertility bulls is a challenge since large variations exist in the result of tests applied for semen evaluation. Therefore, the present study was undertaken to predict the fertility of buffalo bulls on the basis of sperm motion traits, function tests and expression of heparin binding protein (HBP). Both fresh and frozen semen from breeding Murrah buffalo bulls (30) were procured from 2 government bull farms. The frozen-thawed semen was used to evaluate first service conception rate (FSCR), CASA-based motility (total and progressive) and function tests (HOST, acrosome reaction and DNA integrity). On the basis of FSCR, all bulls were divided into 3 groups, viz. good fertility bulls (GFB, >50%), average fertility bulls (AFB, 30-49.9%) and poor fertility bulls (PFB,